MIGRAINE: ESSENTIAL TREATMENT AND PREVENTION PRINCIPLES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Migraine is a disease manifested by attacks of severe headaches. Often, the pain is one-sided, pulsating, increases with physical exertion and may be accompanied by nausea and hypersensitivity to light, sound and smells. The precursors of migraines last from a few minutes to an hour. During this period, a person's balance, sensitivity, coordination of movements, speech and vision may be disturbed. Migraines usually begin during puberty and weaken after 50 years. Tension migraine is an incorrect term that is sometimes used to refer to tension headaches. Tension headaches are associated with stress or musculoskeletal neck problems. This type of headache is characterized by squeezing or squeezing pain, as from a tight bandage around the head. The pain may start from the neck or spread to it.